2019
DOI: 10.18632/aging.101871
|View full text |Cite
|
Sign up to set email alerts
|

Anesthesia and surgery induce cognitive dysfunction in elderly male mice: the role of gut microbiota

Abstract: It is well known that the incidence of postoperative cognitive dysfunction (POCD) is high in elderly patients. The pathogenesis and therapeutic mechanisms of POCD, however, have not yet been completely elucidated. The effects of gut microbiota, particularly in terms of regulating brain function, have gradually attracted increasing attention. In this study, we investigated the potential role of gut microbiota in POCD in aged male mice and attempted to determine whether alterations in gut microbiota would be hel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(40 citation statements)
references
References 38 publications
1
38
1
Order By: Relevance
“…Furthermore, the results of the LEfSe analysis in female and male 3xTg-AD mice at 3 and 5 months old in fecal samples, show bacteria with a statistically significant change in LDA scores such as Xanthomonadaceae , Oxalobacteraceae , Streptomycetaceae , Koribacteraceae , and Streptomycetaceae families, Gemella , Dehalobacterium , Clostridium , Allobaculum , Selenomonas , Veillonella , Lactococcus , Desulfovibrio , Bradyrhizobium , Campylobacter , Erythrobacter , Neisseria , Flexispira , Microbacterium , Collinsella , Atopobium , Pedobacter , and the S1 genera. These microorganisms have been associated with both pre-clinical models and patients who present AD mainly; however, other bacteria are related to aging, cognitive decline, cerebral damage, and inflammatory response in mice and humans ( Thomas et al, 2012 ; Wang et al, 2016 ; Bonfili et al, 2017 ; Harach et al, 2017 ; Morris et al, 2017 ; Vogt et al, 2017 ; Zhang et al, 2017 ; Aguayo et al, 2018 ; Alonso et al, 2018 ; Antonets et al, 2018 ; Bäuerl et al, 2018 ; Dong et al, 2018 ; Zhuang et al, 2018 ; Haran et al, 2019 ; Li et al, 2019 ; Zhan et al, 2019 ; Beydoun et al, 2020 ; Na et al, 2020 ; Westfall et al, 2020 ). These results suggest that bacteria families and genera are representative microorganisms of gut microbiota of disease that could be considered a useful tool for diagnostic as well as a progression biomarker of AD.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the results of the LEfSe analysis in female and male 3xTg-AD mice at 3 and 5 months old in fecal samples, show bacteria with a statistically significant change in LDA scores such as Xanthomonadaceae , Oxalobacteraceae , Streptomycetaceae , Koribacteraceae , and Streptomycetaceae families, Gemella , Dehalobacterium , Clostridium , Allobaculum , Selenomonas , Veillonella , Lactococcus , Desulfovibrio , Bradyrhizobium , Campylobacter , Erythrobacter , Neisseria , Flexispira , Microbacterium , Collinsella , Atopobium , Pedobacter , and the S1 genera. These microorganisms have been associated with both pre-clinical models and patients who present AD mainly; however, other bacteria are related to aging, cognitive decline, cerebral damage, and inflammatory response in mice and humans ( Thomas et al, 2012 ; Wang et al, 2016 ; Bonfili et al, 2017 ; Harach et al, 2017 ; Morris et al, 2017 ; Vogt et al, 2017 ; Zhang et al, 2017 ; Aguayo et al, 2018 ; Alonso et al, 2018 ; Antonets et al, 2018 ; Bäuerl et al, 2018 ; Dong et al, 2018 ; Zhuang et al, 2018 ; Haran et al, 2019 ; Li et al, 2019 ; Zhan et al, 2019 ; Beydoun et al, 2020 ; Na et al, 2020 ; Westfall et al, 2020 ). These results suggest that bacteria families and genera are representative microorganisms of gut microbiota of disease that could be considered a useful tool for diagnostic as well as a progression biomarker of AD.…”
Section: Discussionmentioning
confidence: 99%
“…The MWM is a commonly used task for assessing spatial learning and memory in models of neurodegenerative disorders [24]. In the present study, diabetic mice could be stratified into CD and Non-CD groups using the hierarchical cluster analysis of MWM performance indices [17]. Previous studies have reported CD in diabetic mice [20, 25]; however, in the present study, we excluded those without CD to distinctly reveal associations with specific diabetes-related changes (in this case, gut microbiota).…”
Section: Discussionmentioning
confidence: 99%
“…Our previous study has demonstrated that CD in SAMP8 mice was strongly associated with gut microbiota composition and relative abundance [16]. Further, we have observed a substantial difference in gut microbiota composition among aged mice with CD after surgery and anesthesia [17]. In the present study, we observed no significant difference in α-diversity (consisting of Shannon and Simpson indices) among the control, CD, and Non-CD groups, suggesting little change in bacterial numbers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Spatial learning and memory function were assessed using the Morris water maze test (Zhan et al 2019). Briefly, mice were trained four times each day for five consecutive days in a circular pool where each mouse was permitted 60 s to find the hidden platform, which was 10 cm in diameter and submerged 1 cm below the water surface in the target quadrant.…”
Section: Cognitive Functionmentioning
confidence: 99%